Greener Greens? - Clarke, R (Open Schools Journal for Open Science, 2019)
Are current consumer patterns sustainable in terms of our planet’s health? Do the food choices we make have a negative impact on climate change? Is the demand for farmland affecting biodiversity? Here, we the students of Confey College, report the findings of our investigations into these and other questions related to our impact on the environment at a local and global level.